Die Protek AG und die Konsolidierung der Medizintechnikindustrie: Interview mit Rolf Soiron (Maurice E. Müller und die Entwicklung künstlicher Hüftgelenke in der Schweiz. Zeitzeugenbefragungen zur Geschichte einer Medizintechnik, 2023)
Rolf Soiron was CEO of Protek AG from August 31, 1983 to July 31, 1987. As a member of the Board of Directors of Stratec AG (1995-2005), Soiron was involved in the merger of this medical technology company with the orthopaedics company Synthes USA to form Synthes-Stratec AG. Both companies had emerged at different times from the osteosynthesis business of Institut Straumann AG, which had been created in 1960 through collaboration with the Arbeitsgemeinschaft für Osteosynthesefragen.